Physicochemical Properties of Pasteurized Cow's Milk: Review - Rahmadini, Annisa’ Suci; Asben, Alfi; Dewi, Kurnia Harlina; Ernita, Yuni (Green Engineering Society, 2024)
The purpose of pasteurization of milk is to improve the quality of the milk, kill pathogenic and non-pathogenic bacteria. The heating process is carried out to eliminate pathogenic microorganisms in milk, but pathogenic microorganisms can grow again after processing and packaging milk. Based on this, it is necessary to test the safety level of pasteurized milk. An important test that needs to be carried out is the physicochemical properties. The results of testing pasteurized milk using a cold chain showed a pH of 6.7, protein content about 2.67%, and fat content about 3.37%. The influence of pasteurized milk storage conditions on its physicochemical properties also needs to be tested. The test results showed that the acidity of pasteurized milk increased during two days of storage at 20°C from 0.142 ± 0.00119% to 0.162 ± 0.00342%, the pH was lowered by 0.068 units, the average electrical conductivity (EC) increased from 5.220±0.0397 mS/cm to 5.880±0.1006 mS/cm. Increasing temperature and storage time causes an increase in phosphate ions and lowers pH rapidly, because acidification of milk causes changes in salt balance. Physical and sensory quality tests of pasteurized milk products were also carried out to determine the effect of temperature and transportation time. The test results explained that at 72 hours of transportation with a temperature of 5oC the pH value was 6.7-6.8. These results indicate that the pH of pasteurized milk still complies with SNI, this condition is also supported by the sensory condition which is still normal.